Interferon Beta-1b Level in Parkinson’s Disease: Before and After SARS-CoV-2 Vaccination - Donmez Cakil, Yaprak; Ozunal, Zeynep Gunes; Karsidag, Sibel; Åžahin, Sevki (International Clinical Neuroscience Journal, 2022)
Background: Parkinson’s disease (PD) is a neurodegenerative disease. Immune response varies after vaccination in different patients. We aimed to evaluate interferon beta-1b (IFNβ-1b) level in patients with PD in response to inactivated SARS-CoV-2 (CoronaVac) vaccination. Methods: Eight patients with the diagnosis of idiopathic PD and followed in the outpatient clinic (stages 1-2) were enrolled. Total blood count was performed before vaccination. IFNβ-1b levels were measured by ELISA and motor examination was performed before and two hours after vaccination. Results: IFNβ-1b levels increased in three patients, whereas no change was detected in one patient and the levels decreased in four patients. Divergent responses were found related to the time of diagnosis. Conclusion: The time of PD diagnosis, as well as the age of the patients, may be responsible for the variability of the post-vaccine immune response.